Using Question Answer Relationship (QAR) Strategy On Students’ Narrative Reading Comprehension Achievement On Eighth Grade Of SMP Negeri 14 Palembang - Hilwani Rahmi; Dalilan Dalilan; Mirrah Salsabila (Indonesian Journal of Innovation Multidisipliner Research, 2026)
This study aimed to investigate the effect of the Question Answer Relationship (QAR) strategy on students’ reading comprehension in narrative texts. This research used a quantitative quasi-experimental design with a pre-test and post-test non-equivalent group design involving 68 eighth-grade students at SMP Negeri 14 Palembang. The results showed that both groups improved; however, the experimental group showed a more significant increase. The control group’s mean score rose from 47.82 to 60.03, while the experimental group improved from 51.97 to a higher level categorized as good, with most students (52.9%) achieving this level. Statistical analysis revealed a significant difference between the groups (p < 0.05). Therefore, the QAR strategy is effective in improving students’ reading comprehension and is recommended for teaching narrative texts. Keywords: QAR Strategy, Reading Comprehension, Narrative Text, Quasi-Experimental Study